2022
DOI: 10.3390/diagnostics12030727
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Intraoperative OCT-Assisted Lamellar Corneal Transplants: A Game Changer?

Abstract: Intraoperative optical coherence tomography (iOCT) is a noninvasive imaging technique that gives real-time dynamic feedback on surgical procedures. iOCT was first employed in vitreoretinal surgery, but successively served as a guidance in several anterior segment surgical approaches: keratoplasty, implantable Collamer lens (ICL) implantation, and cataract surgery. Among all of those approaches, the unbeatable features of iOCT are fully exploited in anterior and posterior lamellar keratoplasty, and the purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…This means variability in outcomes could potentially be less if a different setup was used. Second, the time horizon is 6 months postoperatively, which means long-term effects cannot be directly measured, although previous RCTs and real-world studies show little to no difference in graft survival between 6 and 12 months (Chamberlain et al, 2019;Dunker et al, 2020;Schlögl et al, 2016). For the cost variability, we report on the robustness present at 6 months using sensitivity analyses but expected costs after 6 months are not included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means variability in outcomes could potentially be less if a different setup was used. Second, the time horizon is 6 months postoperatively, which means long-term effects cannot be directly measured, although previous RCTs and real-world studies show little to no difference in graft survival between 6 and 12 months (Chamberlain et al, 2019;Dunker et al, 2020;Schlögl et al, 2016). For the cost variability, we report on the robustness present at 6 months using sensitivity analyses but expected costs after 6 months are not included.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have observed that the utilization of iOCT in corneal surgery could increase clinical performance, increase the safety of DMEK surgery and aid in surgical decision‐making (Carlà et al, 2022; Cost et al, 2015; Dunker, Dickman, et al, 2021; Dunker, Veldman, et al, 2021; Pasricha et al, 2015; Sharma et al, 2020). Also, corneal transplantations are known to be cost‐effective, increase health utility and different transplantation techniques are compared before in cost‐effectiveness analyses (Beauchemin et al, 2010; Bose et al, 2013; Prabhu et al, 2013; Shah et al, 2021; Simons et al, 2019, 2022; van den Biggelaar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative optical coherence tomography (iOCT) is used extensively in complex anterior segment surgery, providing increased precision and thereby more safety and improved clinical outcomes. In lamellar keratoplasty, the successful application of iOCT has already been described 1 . For example, the iOCT can be used for defining the cutting depth of deep anterior lamellar keratoplasty (DALK) or for visualization of potential fluid in the interface in Descemet stripping automated endothelial keratoplasty (DSAEK) 2 , 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for the correct corneal graft positioning in Descemet membrane endothelial keratoplasty (DMEK), a marker was previously required. The iOCT allows recognition of the corneal graft orientation and further observation of the unfolding process of the graft without the need for marking [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In addition, intraoperative anterior segment optical coherence tomography (AS-OCT) enables corneal visualization during DALK, offering real-time information for surgical planning and optical instrument localization which helps in reducing surgical complications and obtaining a more precise stromal dissection. 5…”
mentioning
confidence: 99%